Case history on excessively large displacements and remediation of pile-supported excavation in a sloping ground. (January 2023) - Skejić, Adis; Balić, Anis; Kapor, Mladen
Highlights: A deep excavation case study describing excessive displacements is investigated, and mitigation measures are described and implemented on-site. The probable causes of the failure are discussed and clarified. Even for well-known local geological engineering conditions, a thorough site investigation is inevitable to prevent failure. Complex, time-consuming 3D numerical analysis significantly contributes to understanding soil-structure interaction mechanisms. The lessons learned summarized serve to prevent future failures of similar structures. Abstract: Pile-supported excavations in urban region slopes can result in excessively large retaining wall and ground surface displacements if not strutted or tied back correctly. Such an example is presented in this study showing the details of investigation works, construction procedure, monitoring, and 3D numerical analysis of a deep excavation in a stiff clay slope. Total excavation depth ranged from 4.8 m to 5.3 m, with additional 2.0 m high vertical wall and 2.8 m high steep slope in the vicinity of the pile capping beam. Before reaching the bottom of the designed excavation, the maximum cumulative monitored wall displacements were 115.0 mm, while the cracks observed on the nearby uphill structures exceeded 5.0 mm in width. Detailed field inspections and the 3D numerical analysis were performed to investigate the displacement pattern of the pile wall and the adjacent soil and structures in the uphill area. The numerical model results were further used to define specific supporting measures to enable excavation and building construction. Supporting measures were presented, and their effectiveness was assessed. Finally, the lessons learned were summarized to prevent future failures of similar structures.